MENONGKAH KERANG PADA SUKU DUANU DI DESA TANJUNG PASIR KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR - Amrina Rosada; Kamaruddin '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Duanu tribe is community of laut tribe or sea people where located in Muara Sungai Indragiri Hilir, also part of Kelompok Adat Terpencil (KAT), it is a part of Ras Proto Melayu (Melayu Tua). Duanu tribe have an unique tradition, that is Menongkah Kerang. Menongkah Kerang is technique of Duanu tribe to looking for shell in muddy beach when the receding of sea water coming using piece of board that they named with papan tongkah. This research have purpose to knowing about: (1) To knowing about history of Duanu tribe in Desa Tanjung Pasir, Kecamatan Tanah Merah, Kabupaten Indragiri Hilir. (2) To knowing about development menongkah kerang tradition of Duanu tribe in Desa Tanjung Pasir, Kecamatan Tanah Merah, Kabupaten Indragiri Hilir. (3) To knowing about parents role and youth in there to preserve Menongkah Kerang tradition of Duanu tribe in Desa Tanjung Pasir, Kecamatan Tanah Merah, Kabupaten Indragiri Hilir. This research is qualitative descriptive and technique of data accumulation using observation technique, interview, documentation and documents. Result of this research showing that Menongkah Kerang already run into progress, which one, this menongkah karang have become the yearly travel destination in Kabupaten Indragiri Hilir and also already there are menongkah traditional dance that be showed at cultural festival event and tradition events in Indragiri Hilir.Keywords: Menongkah Kerang, Duanu Tribe